Monitoring digoxin therapy: I. Plasma concentrations and an in vitro assay of tissue response. - Aronson, J; Grahame-Smith, D; Hallis, K; Hibble, A; Wigley, F (1977)
1 An in vitro technique is described for measuring the uptake of 86Rb by human erythrocytes. 2 Fifteen patients were treated with digoxin for atrial fibrillation and other fast arrhythmias. 3 86Rb uptake by the patients' own red cells fell from pre-treatment values during digitalization. 4 The therapeutic response of patients with atrial fibrillation correlated better with the changes in 86Rb uptake than with plasma digoxin concentrations.